Estructura arbórea e índice de valor de importancia en un bosque de colina baja, distrito de San Pablo, Loreto, Perú. 2024 - Campos Rivera, Favio Sebastian (2025)
An analysis of tree structure and importance value index was carried out in a low hill forest, within the General Forest Management Plan (PGMF) 16-IQU/C-J-034-04, located in the district of San Pablo, Loreto, Peru. Thirty-four tree species, 34 genera and 18 botanical families were identified, with a total of 457 individuals recorded. The 60 to 69 cm diameter category accounted for most of the trees, with 24,51%, followed by the 70 to 80 cm class, which reached 19.4%. In contrast, the 40 to 50 cm class shows the smallest proportion, with only 1,53%. Gavarretia terminalis and Parkia aff. panurensis stand out as having the highest average heights, with 26.00 and 25.58 meters, respectively. The class with diameters greater than 90 cm has the highest average height (25.76 m), while the 10 to 20 cm class has the lowest average height (12.17 m). Eschweilera albiflora emerges as the dominant species, with a basal area of 10.29 m²/ha, followed by Cedrelinga cateniformis with 8.87 m²/ha. On the other hand, Caryocar microcarpum and Handroanthus chrysanthus have the lowest values, with 0,05 m²/ha and 0,04 m²/ha, respectively. The species with the highest importance value index are Eschweilera albiflora (32,20%) and Allantoma decandra (23,27%), reflecting their predominance in terms of abundance, dominance and frequency. In contrast, Handroanthus chrysanthus (2.30%) and Calophyllum longifolium (1,21%) exhibit the lowest values.